ANALISIS PENERAPAN GAYA MENGAJAR EXPOSITION STYLE DALAM PENINGKATAN KEAKTIFAN SISWA KELAS IV SEKOLAH DASAR - Yustia Zahra, Fanny; Sarifah, Iva; Banindra Yudha, Chrisnaji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
One of the problems that often occurs in the classroom is students who are not active. One of the influencing factors is variations in teacher teaching styles. In this research, researchers will analyze the application of the exposition style teaching style in increasing student activity. This research aims to find out how to increase student activity by using the exposition style of teaching. The research methodology used in this research is a qualitative approach which will be analyzed descriptively. The results obtained from this research are that the exposition style teaching style used by the teacher can increase student activity compared to lectures. Students feel happy if they can ask and answer the teacher's questions freely. Keywords: student activity, teaching style, exposition style